2012
DOI: 10.1080/03632415.2012.687263
|View full text |Cite
|
Sign up to set email alerts
|

Emulating Riverine Landscape Controls of Beaver in Stream Restoration

Abstract: Stream and floodplain restoration at the reach scale has ranged from expensive, heavy‐handed modification of the channel and floodplain to simple, longer‐term revegetation efforts. We have developed and implemented a simple approach that emulates the ecosystem engineering effects of beaver. This approach is less expensive and disruptive than typical large‐scale engineering efforts and has the potential to restore both fish habitat and floodplain vegetation more rapidly than simply revegetating and waiting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…In a similar study from semi‐arid Idaho, DeVries et al . () documented increased frequency of overbank flows (i.e. hydrologic connectivity with the floodplain) around artificial structures constructed to imitate beaver dams.…”
Section: Abiotic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study from semi‐arid Idaho, DeVries et al . () documented increased frequency of overbank flows (i.e. hydrologic connectivity with the floodplain) around artificial structures constructed to imitate beaver dams.…”
Section: Abiotic Effectsmentioning
confidence: 99%
“…Somewhat limited empirical evidence from temperate streams supports this hypothesis (reviewed in Pollock et al, 2003;Rosell et al, 2005), but few data are available from dryland streams. Where management goals include reducing erosion or sedimentation, promotion of beaver dams may be an effective strategy (DeVries et al, 2012). However, in many dryland river systems, large peak flows are important in conservation of native fish (Rinne and Miller, 2006) or plant (Stromberg, 2001) communities.…”
Section: Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown the ability of beaver dams to have a significant impact on each of these areas. As a result, many restoration projects are beginning to use beaver and beaver dam structures as an ecological and cost‐effective approach in restoration and management (Andersen & Shafroth, ; Burchsted et al , ; Curran & Cannatelli, ; DeBano & Heede, ; DeVries et al , ; Pollock et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent decades have witnessed growing interest in employing or mimicking the remarkable engineering abilities of beaver (Castor canadensis and C. fiber) in stream restoration efforts (Pollock et al 2007;DeVries et al 2012). Recent decades have witnessed growing interest in employing or mimicking the remarkable engineering abilities of beaver (Castor canadensis and C. fiber) in stream restoration efforts (Pollock et al 2007;DeVries et al 2012).…”
Section: Introductionmentioning
confidence: 99%